Efektivitas Implementasi Sistem Elektronik (e-Kinerja) Dalam Menilai Kinerja ASN di Kota Padang - Madhani, Liona; Zai, Pretty Novita; Utami, Maulidya Alfi; Hanoselina, Yulia (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This research aims to evaluate the effectiveness of the implementation of an electronic system (E-Kinerja) in assessing the performance of the State Civil Apparatus (ASN) in Padang City. With increasing demands for transparency and accountability in government management, it is hoped that E-Kinerja can be a solution in assessing ASN performance objectively and efficiently. The research method used is by using literature review methods and analysis of relevant written documents. This research identifies the advantages and disadvantages of the e-kinerja system being implemented. Through collecting data from various sources, including government policies, performance reports, and previous studies, this research found that e-kinerja can increase transparency and accountability in ASN performance assessments. The research results show that E-Kinerja in assessing ASN performance in Padang City has a positive impact in increasing the accuracy of performance assessments, facilitating the evaluation process, and increasing ASN work motivation. However, there are still several obstacles to its implementation, such as limited technological infrastructure and low levels of digital literacy among ASN. The conclusion of this research emphasizes the importance of increasing socialization and training on the use of E-Kinerja to increase the effectiveness of the system and encourage better ASN performance in Padang City.